PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMAS MUJAHIDIN PONTIANAKTAHUN AJARAN 2018/2019 - Khairullah, Khairullah; Syambasril, Syambasril; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was based on learning to write explanatory texts in the Pontianak Mujahidin Private High School. Overall, the planning, implementation and evaluation carried out by the teacher has been systematic, even though there are obstacles experienced by the teacher when teaching but all can be handled well. Indonesian language subject teachers are very responsive to the problems that occur around the school and when conducting the learning process. The method used in this research is descriptive method with the form of qualitative research, and the type of teaching research. This study describes the planning, implementation, and learning outcomes of writing explanatory texts carried out by the teacher on the first semester XI grade students of Pontianak Mujahidin High School. The data sources in this study were Indonesian language teachers and students at the Pontianak Mujahidin High School. The data of this study are the results of observations of the plan for the implementation of learning and implementation of learning as well as the results of student learning evaluations. Based on the results of the analysis carried out it can be concluded that the planning made by the teacher is in accordance with the planning component which includes core competencies, basic competencies, objectives, material, methods, media, and assessment instruments.Â Keywords: Â Learning to Write Explanatory Text